The impact of pollen movement on identity preservation of maize (Zea mays) - Chetty, Lukeshni (University of the Free State, 2004)
Maize is an economically important crop in Africa including South Africa. To maintain and produce maize varieties with specific agronomic traits and qualities, management is required in the form of identity preservation (IP). Identity preservation is becoming increasingly important with the advent of modern biotechnology. The purpose of IP is to minimize gene flow of which the principal factor is pollen movement. Maize pollen movement has been previously studied measuring out-crossing, measuring pollen concentrations and computer modelling. In this study, genotypic detection of trapped pollen as well as the phenotypic observation of out-crossing was used. Field trials were performed at two geographic locations in South Africa and spatial as well as temporal isolation was used to ensure that surrounding maize production did not influence the result of this study. It was determined that although various methods of pollen preservation were not effective to maintain pollen DNA integrity, storage in CTAB buffer proved successful for up to nine months for PCR analysis. An inexpensive pollen trapping system was devised using Tween 20 coated on glass slides. From pollen trapping experiments it was determined that maize pollen, with a specific genotype, could be detected at up to 400 m from the source even though the pollen load on the traps was low. Phenotypic evaluation of out-crossing revealed a very high incidence (between 22.3 and 39.1%) of out-crossing between yellow and white adjoining maize rows, and decreased to 1% at a distance of 25 m, and thereafter was an average of 0.36% up to 81.6 m. The two geographic locations were not significantly different in terms of out-crossing data. The analysis of out-crossing data over distance, determined that distance is not solely responsible for the pattern of out-crossing. The analysis of weather data taken during the flowering period indicated that temperature and relative humidity were not significantly different across the different locations. However, wind differed significantly between the different locations with more relevant wind, regarding the orientation to maize plots, in Delmas than in Lichtenburg. Low levels of out-crossing were detected using PCR that would otherwise have remained undetected. The 35S promoter from the Bt gene was detected at 0.12 and 0.9%, respectively, across the different locations, in sampled cobs of white maize up to a distance of 2 m. The quantification of the Bt gene in yellow hybrid seed was consistent with expected values, taking the development of the yellow maize parent into consideration. During the course of this study different areas of research were identified that have not been addressed adequately in this or other studies, this includes, in hind sight, several ways in which the experimental design of this study could have been improved. The assessment of the impact of individual environmental variables on pollen longevity warrants a more detailed study. The correlation between pollen DNA viability and fertilisation potential should be further investigated. It would also be useful to have included data over multiple years but was not possible due to the time constraints of an M.Sc. In conclusion, this study has determined that maize pollen of a specific genotype can be detected at 400 m from its source and that even though out-crossing declines rapidly up to 25 m, out-crossing events average 0.36% up to 81.6 m. Out-crossing is determined by distance in conjunction with environmental factors, making geographic specific data important for region specific identity preservation requirements. This study makes an important contribution to available data on pollen movement, as no other published data is available for South Africa.
Keywords: Pollen -- Biotechnology; Corn -- Genetic engineering; Corn -- Breeding; Dissertation (M.Sc. (Microbial, Biochemical and Food Biotechnology))--University of the Free State, 2014